Bone Mineral Density and Vitamin D Status in Elderly Javanese Women - Lusiana Batubara; Faizah Fulyani; Dwi Ngestiningsih; Hermina Sukmaningtyas; Ainun Rahmasari Gumay; Etisa Adi Murbawani; Enny Probosari (Jurnal Kedokteran Diponegoro, 2023)
Background: Vitamin D (25OHD) works as a lipid-soluble secosteroid hormone essential for metabolic activities, including bone mineralization. 1,25OHD and its receptor are transcription factors for various bone homeostasis genes. Numerous studies have connected vitamin D insufficiency with a decline in bone mineral density (BMD), but the results are still conflicting. However, information on vitamin D insufficiency among Indonesian individuals is hardly available.